Kierkegaard's Journals and Notebooks Volume 10 : Journals NB31-NB36 - Kierkegaard, Soren, 1813-1855 (Book collections on Project MUSE., 2018)
For over a century, the Danish thinker Soren Kierkegaard (1813-55) has been at the center of a number of important discussions, concerning not only philosophy and theology, but also, more recently, fields such as social thought, psychology, and contemporary aesthetics, especially literary theory. Despite his relatively short life, Kierkegaard was an extraordinarily prolific writer, as attested to by the 26-volume Princeton University Press edition of all of his published writings. But Kierkegaard left behind nearly as much unpublished writing, most of which consists of what are called his "journals and notebooks." Kierkegaard has long been recognized as one of history's great journal keepers, but only rather small portions of his journals and notebooks are what we usually understand by the term "diaries." By far the greater part of Kierkegaard's journals and notebooks consists of reflections on a myriad of subjects--philosophical, religious, political, personal. Studying his journals and notebooks takes us into his workshop, where we can see his entire universe of thought. We can witness the genesis of his published works, to be sure--but we can also see whole galaxies of concepts, new insights, and fragments, large and small, of partially (or almost entirely) completed but unpublished works. Kierkegaard's Journals and Notebooks enables us to see the thinker in dialogue with his times and with himself. Kierkegaard wrote his journals in a two-column format, one for his initial entries and the second for the extensive marginal comments that he added later. This edition of the journals reproduces this format, includes several photographs of original manuscript pages, and contains extensive scholarly commentary on the various entries and on the history of the manuscripts being reproduced. Volume 10 of this series includes the final six of Kierkegaard's important "NB" journals (Journals NB31 through NB36), which cover the last months of 1854, a period when Kierkegaard made the final preparations for and the initial launch of his furious assault on the established church. But in addition to this incendiary material, these journals also contain a great trove of his reflections on theology, philosophy, and the perils and opportunities of modernity